PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR DALAM PENGUKURAN KINERJA (Studi Kasus Pada RSUD dr. Wahidin Sudiro Husodo Kota Mojokerto) - ‘Ulya, Eva Choirul; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2014)
This  research  aims  to  measure  the  performance  of  RSUD  dr.  Wahidin Sudiro Husodo Mojokerto using  the balanced  scorecard method. There are  four perspectives  in  a  balanced  scorecard  measurement:  financial  perspective, customer  perspective,  internal  business  perspective,  and  learning  and  growth perspective.  This  research  uses  primary  data  by  spreading  questionnaires  to patients  and  employees  of  RSUD  dr.  Wahidin  Sudiro  Husodo  Mojokerto,  and using secondary data  including  financial statements,  the number of patients, and employee  attendance  data,  during  2010  through  2013.  Internal  business perspective  shows  good  result,  customer  perspective  and  financial  perspective show  quite  good  result,  but  learning  and  growth  perspective  shows  below standard result. Seen  from  four perspectives of balanced scorecard method, over all performance of RSUD dr. Wahidin Sudiro Husodo Mojokerto is good enough. Keywords:  general hospital, balanced scorecard